Bagworm, Thyridopteryx ephemeraeformis Haworth (Insecta: Lepidoptera: Psychidae) - Brooke L. Moffis; Steven P. Arthurs (EDIS, 2013)
North American bagworm can feed on over 50 families of deciduous and evergreen trees and shrubs. Severe infestations can damage the aesthetics and health of host plants, especially juniper and arborvitae species. Many of the preferred host plants do not grow well below the USDA hardiness zone 8A, but due to its wide host range, high female fecundity, and method of dispersal, bagworm can still be problematic in the Florida landscape. This 5-page fact sheet was written by Brooke L. Moffis and Steven P. Arthurs and published by the UF Department of Entomology and Nematology, March 2013.